KAJIAN KUALITAS AIR SUNGAI YANG MELEWATI KECAMATAN GAMBUT DAN ALUH ALUH KALIMANTAN SELATAN - Byna Susanto; Krisdianto Krisdianto; Hasrul Satria (Bioscientiae, 2009)
Research about river water quality study passing Kecamatan Gambut and Aluh Aluh has been done in river residing in Kecamatan Gambut and Aluh Aluh Kalimantan Selatan in finite October of December 2008. Purpose of this research is to study river water quality passing Kecamatan Gambut and Aluh Aluh based on physics parameter, chemistry, and microbiology. Sample collected from 4 station, that is station 1 in Handil Malang, station 2 in Tambak Sirang Baru, station 3 in Bunipah and station 4 in Handil Parit. This research applies method survey, water sampling with method purposive sampling is done counted 3 times retrieval in each station with international 2 week once. Quantitative data collected from result of measurement analysis of physics parameter (temperature, TSS, TDS, turbidity, salinity), chemistry parameter ( hydrogen ion exponent, DO, BOD, COD, iron (Fe), manganese (Mn), nitrate, nitrite, ammonia), and microbiology parameter (total Coliform, and Colitinja/Escherichia coli). Result of research from fourth of station shows value TDS ( 233,7-1966,7 mg/L), turbidity ( 5,07-83,2 NTU), degree of acidity ( hydrogen ion exponent) ( 3,09-6,45), DO ( 1,8 - 4,3 mg/L), biochemical oxygen demand BOD ( 3,67-22,93 mg/L), COD ( 2,3-88,62 mg/L), iron ( Fe) ( 0,45 - 8,11 mg/L), manganese ( Mn) ( 0,03-52,3 mg/L), nitrite ( 0,00-0,46 mg/L), ammonia ( 0,64 - 2,7 mg/L), and bacterium quantitative analysis Coliform ( 18.000-170.000 MPN/100 ml), Colitinja/Escherichia coli (< 180-92000 MPN/100 ml). Test result to parameter is upper showing result which has exceeded standard boundary threshold quality of river water for drinking water (Class I) according to Peraturan Gubernur Kalimantan Selatan No.05 the year 2007.